Pengaruh Kode Etik Profesi, Love Of Money, Religiusitas Terhadap Persepsi Etis Mahasiswa Dengan Gender Sebagai Pemoderasi - Ni Putu Febry Widiantari; Ni Ketut Rasmini (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research aims to empirically test the influence of professional codes of ethics, love of money, religiosity on students' ethical perceptions with gender as a moderator. The population in this research is all active students of the 2019 accounting study program at Udayana University. The sampling method used in this research is the saturated sampling technique (census) found in NonProbability Sampling. The respondents in this research were 54 active students of the 2019 accounting study program. Data was collected through questionnaires distributed directly to respondents. The data analysis technique used to test the hypothesis in the research is moderated regression analysis (MRA). Moderated regression analysis is a regression analysis that involves moderating variables in building a relationship model. The results of data analysis show that the professional code of ethics and religiosity have a positive effect on students' ethical perceptions, whereas in the research results the love of money variable has a negative effect on students' ethical perceptions, then the gender variable is unable to moderate the relationship between the professional code of ethics, love of money, and religiosity. Accounting students' ethical perceptions. Keywords : Professional Code Of Ethics, Love Of Money, Religiosity, Ethical Perception, Gender.